Vox clamantis in deserto: Rhetoric, Reproach, and the Forging of Ascetic Authority in Jerome's Letters from the Syrian Desert - Cain, Andrew (The journal of theological studies, 2006)
In eight letters (Epp. 6–9, 11–13, 16) that Jerome sent from his monastic retreat in the Syrian desert between c.375 and c.377, he sharply criticized friends who were not as faithful in writing to him as he had been to them. John Kelly, in his influential biography of Jerome (1975), famously read these letters as the petty outbursts of a neurotic curmudgeon who was bitter and resentful about being snubbed; other scholars since have followed suit with this face-value interpretation. The present article challenges this widely accepted psychologizing reading as being uncritical and unappreciative of the letters as literary artefacts. It is demonstrated first that they are stylish specimens of the epistolary genre of reproach. It is then argued that these letters, inasmuch as they portray Jerome as being shunned by human society, were important components of a book of collected personal correspondence that Jerome released in Rome in the early 380s to promote himself as the consummate hermit and hero of desert asceticism. An earlier version of this essay was read in January 2004 at the Annual Meeting of the American Philological Association in San Francisco. A later version was delivered as an invited lecture to the Department of Classics at Columbia University in March 2005. I would like to thank Charles Brittain, Catherine Conybeare, and Mark Vessey for reading an advanced draft of this article and offering well-met suggestions.